Bismuth modified gamma radiation shielding properties of titanium vanadium sodium tellurite glasses as a potent transparent radiation-resistant glass applications - M.H.M., Zaid; K.A., Matori; H.A.A., Sidek; I.R., Ibrahim (lsevier Korea LLC, 2020)
This work reported the radiation shielding characteristic of the bismuth titanium vanadium sodium tellurite glass system. The density of the specially-developed glass samples was increased from 2.21 to 4.01 g/cm3 with the addition of Bi2O3, despite the fact the molar volume is decease within 85.43–54.79 cm3/mol. The WinXcom program was used to approximate the effect of Bi2O3 on the gamma radiation shielding parameters of bismuth titanium vanadium sodium tellurite glasses. The μm values decrease with the increase of Bi2O3 concentration. The computed data shows that the glass sample with 20 mol.% of Bi2O3 content has the greatest radiation attenuation performance in comparison to other selected glasses. The Bi2O3–TiO2–V2O5–Na2O–TeO2 glass system shows excellent neutron shielding material with high long-term light transmittance and discharge resistance and could be potentially used as transparent radiation-resistant shielding glass applications.